GANG SEBAGAI PUSAT NILAI LOKALITAS KEHIDUPAN MASYARAKAT KAMPUNG KOTA: Studi Kasus: Kampung Keputran Pasar Kecil, Surabaya - Herson J. Chandra; Rony G. Sunaryo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2019)
Title: Alley as the Center/ Generator of Locality Values of the Community Life in Urban Kampong The people in the urban kampong as part of settlement area with rather high intensity tend to maximize their property. The community along with their value system build and develop spaces following their particular meaning. Through this research the spaces as the embodiment of the local life in physical form in Kampong Keputran would be observed and aimed to find the meaning of it. This study will use Regionalism of Indonesia Architecture as one of the approach to find the local values that lives in the kampong, and Spatial Recoqnition as an operational theory applied to study and to get the community understanding about values perceived in this settlement area. This study would be a library research using data as documentation drawings of the existing condition, and also research journal as supportive information. The result of this research would be finding on the most dominant spaces that influencing the quality of social life in kampong. This result could be used as a design criteria for a multi story housing that accomodating the local values of urban kampong community. And hopefully there will be more understanding about how the community give meaning to the space in the kampung as their living space.